A framework of good governance in regulating religious extremism to improve national security in Malaysia - Akhmetova, Elmira; Aminudin, Rabi'ah; Ahmad H.Osman, Rahmah; Ahmad, Nadzrah; S.Shikh @ Sy Sheikh, Sharifah Syahirah (IIUM Press, International Islamic University Malaysia, 2020)
This research aimed at constructing a framework for regulating religious extremism in Malaysia based on principles of good governance. The first stage of the research provided a general study into the definitions of extremism and religious extremism. It found that religious feelings can be utilised by terrorist organizations and radical movements to mobilize the masses. The research further observed that religious extremism is becoming a severe concern in Malaysia, which was for decades hailed as an oasis of moderate Islam. The second stage of the research analysed the factors contributing to the rise of religious extremism in Malaysia using a quali-quantitative method that incorporated survey data gathered in KL in 2019 by the authors, three expert interviews, and secondary literature. The research identified two levels of factors, individual and socio-cultural/governance, that contribute to the spread of extremist understanding of religion. It found that human behaviour has become more receptive to violence and that the individual and collective understanding of religion has become more radical today due to personal grievances, social environment and global realities. Thus, the process of reducing extremism and radicalism in Malaysia should encompass the individual, societal and transnational stratum. Extremism and radicalization of societies could be the manifestation of the absence or weakness of good governance. Thus, the last stage of the research aimed at constructing a framework for regulating religious extremism in Malaysia based on good governance principles. It suggested that adhering to good governance assists authorities in regulating societies’ immoderate behaviour by providing wellbeing, safety and happiness to the overwhelming majority of the population. This proposed framework can provide a moderate and authentic understanding of Islamic principles and serve as an instrument in creating an amicable and harmonious social and political environment in Malaysia. This framework can improve national security by promoting the basic principles of good governance such as transparency, participation, equality, justice, moderation and accountability, which are ingrained in the spirit of Islam.